2009
DOI: 10.1152/ajpregu.90890.2008
|View full text |Cite
|
Sign up to set email alerts
|

Drinking-induced thermoregulatory panting in rehydrated sheep: influences of oropharyngeal/esophageal signals, core temperature, and thirst satiety

Abstract: Dehydrated mammals conserve body water by reducing thermoregulatory evaporative cooling responses e.g., panting and sweating. Increased core temperature (Tc) may result. Following rehydration and correction of fluid deficits, panting and sweating commence. We investigated the role of oropharyngeal/esophageal, postabsorptive and thermal signals in the panting response, and reduced Tc that occurs when unshorn sheep drink water following water deprivation for 2 days (ambient temperature 20 degrees C). Ingestion o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
20
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 24 publications
(24 citation statements)
references
References 27 publications
3
20
0
1
Order By: Relevance
“…marsupials, 36 °C; cats and dogs, 37-38 °C; and sheep and goats, 39 °C Baker and Dawson, 1985;Jessen et al, 1998;Randall et al, 2002;McKinley et al, 2009). This constancy of core temperature comes about because a number of homeostatic responses are engaged when core temperature changes outside the "thermoneutral range" for that species.…”
Section: Regulation Of Core Temperaturementioning
confidence: 99%
See 4 more Smart Citations
“…marsupials, 36 °C; cats and dogs, 37-38 °C; and sheep and goats, 39 °C Baker and Dawson, 1985;Jessen et al, 1998;Randall et al, 2002;McKinley et al, 2009). This constancy of core temperature comes about because a number of homeostatic responses are engaged when core temperature changes outside the "thermoneutral range" for that species.…”
Section: Regulation Of Core Temperaturementioning
confidence: 99%
“…dogs, cats, sheep, and goats, show that when these animals are subjected to a warm environment, they engage in thermoregulatory panting and/or sweating that results in elevated plasma Na + concentration and osmolality if the evaporated water is not replaced Baker and Dawson, 1985;Baker, 1989;McKinley et al, 2009). Such thermoregulatory loss of body fluids does not continue at the same rate if animals become dehydrated and many investigators have shown that dehydration, brought on usually by water deprivation, results in an attenuation of sweating and/or panting Baker and Dawson, 1985;Baker, 1989;McKinley et al, 2009). For example, exercising cats reduce evaporative heat loss if they are deprived of water compared with those permitted to drink water .…”
Section: Influence Of Dehydration and Hypertonicity On Thermoregulatomentioning
confidence: 99%
See 3 more Smart Citations